The System of Arabic Language Learning in Constructive Perspective Language - Syamsul Hadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
The principal issues are analyzed in this study are to determine the Learning System of Arabic Language Proficiency on Constructive Perspective at MTs N 1 Bantul and MTs Al Falaah Bantul. This research is a descriptive qualitative research through participatory observation. The sample of this research data is 7th grade. The results showed the system and practice of learning Arabic skills in MTs N 1 Bantul and MTs Al Falaah Bantul with a constructive perspective already practiced in each Arabic language proficiency. However, in the Arabic language learning process there are several obstacles, including the lack of student ability to read and wrote Arabic. In addition, the use of existing learning media has not yet been maximized. This obstacle can be overcome by extracurricular reading of the Koran, which is held every Friday at afternoon. As for the optimization of the use of instructional media, the teacher will try even harder to procure learning media.